Edukasi Hipertensi Pada Keluarga Dengan Pengendalian Menggunakan Latihan Relaksasi Otot Progresif Di Wilayah Kerja Puskesmas Kopeta Kecamatan Alok Kabupaten Sikka - Fransiskus Borgias; Wihelmus Nong Baba (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Hypertension is a non-communicable disease which is one of the main causes of death in the world. A person can be said to be diagnosed with hypertension if the systolic blood pressure is at a level of 140 mmHg or more and the diastolic blood pressure is at a level of 90 mmHg or more. Interventions that can be done in preventing and reducing high blood pressure by providing education on controlling progressive muscle relaxation exercises. This study aims to determine the effect of Progressive Muscle Relaxation Exercises on reducing blood pressure in the working area of the Kopeta Health Center, Alok District, Sikka Regency. Methods of data collection techniques through observation, interviews, physical examination and documentation. The results of data analysis showed several diagnoses, namely health behavior tends to be risky, risk of decreased cardiac output, readiness to increase knowledge. Hypertension education with control using progressive muscle relaxation is one of the non-pharmacological interventions that can be used to reduce blood pressure. Conclusion: based on the results of the case evaluation conducted, it was found that the application of progressive muscle relaxation exercises can lower blood pressure slowly, besides that this intervention can have a relaxing effect on Mr. I.B and Mr. F.W.